2020
DOI: 10.9734/bji/2019/v23i430091
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation: Toward the Reduction of the Salinity Stress Effect on Wheat Plants Using NPK Rhizobacteria

Abstract: Salinity is one of the most vicious environmental factors controlling the productivity of crop plants as most of the crop plants are sensitive to salinity affected by high concentrations of salts in the soil. The objective of this study was to evaluate the influence of the inoculation with the encapsulated and liquid culture of three halo-tolerant plants growth-promoting rhizobacteria (PGPR) strains of Paenibacillus polymyxa MSRH5, Bacillus nakamurai MSRH1 and Bacillus pacificus MSR H3 on the growth and yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Many bacterial endophytes can be cultured and can be directly applied to crops either by spraying, seed, or root inoculation [187]. A method for applying salt tolerant bacteria to agricultural production is to use bacterial capsules [188]. Bacterial capsules are polymer-coated outside of the bacteria, and the coating is positively charged and combines with a negatively charged cell wall to form a mixed capsule.…”
Section: Methods To Improve Symbiont Bacteria Utilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many bacterial endophytes can be cultured and can be directly applied to crops either by spraying, seed, or root inoculation [187]. A method for applying salt tolerant bacteria to agricultural production is to use bacterial capsules [188]. Bacterial capsules are polymer-coated outside of the bacteria, and the coating is positively charged and combines with a negatively charged cell wall to form a mixed capsule.…”
Section: Methods To Improve Symbiont Bacteria Utilizationmentioning
confidence: 99%
“…Bacterial capsules are polymer-coated outside of the bacteria, and the coating is positively charged and combines with a negatively charged cell wall to form a mixed capsule. It can be used to improve the survival and persistence of pathogenic bacteria on inoculated crops [188]. Bacterial capsules are non-toxic, durable, convenient, easy to store, and easy to apply.…”
Section: Methods To Improve Symbiont Bacteria Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also of concern is the issue of air quality affected by dust particles, releases significant emissions of gases (methane, hydrogen sulfides, sulfur dioxide and ammonia) offensive odors and other pollutants such as volatile organic compounds (VOCs), particulate matter (PM), nitrogenous compounds during the decomposition of poultry waste that contributed to climate change which is a global concern and deleterious health effects (both chronic and acute) including respiratory conditions (i.e., bronchitis, asthma in children), heart disease, and lung cancer [85,86]. Poultry waste as an important source of nutrients for many edible crops, may also contain some biological hazards that can threaten human health [87]. Poultry waste could be a source of human pathogens such as Salmonella, Campylobacter and Listeria that can potentially contaminate both edible crops and environment, which consequently leads to food-borne diseases [88,89].…”
Section: Health Hazards Pose By Poultry Waste In An Environmentmentioning
confidence: 99%
“…This strain not only helps to mitigate salt toxic effects but also increases plant growth and decreases crop losses due to salinity (Singh et al, 2020) [80] . (Saad et al, 2019) [67] reported that P. polymyxa, B. nakamurai and B. pacificus were effective in colonizing the wheat plant rhizosphere and in protecting wheat plants from destruction to salt stress. Such PGPRs also ameliorated the reduction of proline accumulation in shoots, increased RWC, electrolyte leakage and enzymatic activity, improved antioxidant enzymes, growth and wheat yield under saline stress.…”
Section: Rhizosphere Microbes Improves Plant Stress Tolerance Salinity Tolerancementioning
confidence: 99%